Fallopian tube stem cell medium of porcine and bovine: In vitro regenerative effect on maturation and parthenogenesis of porcine oocytes. (November 2021) - Liu, Kang-You; Lin, Kun-Yi; Lin, Tzu-Yi; Hii, Ling-Yien; Tseng, Hui-Sen; Shen, Perng-Chih; Chang, Shen-Chang; Chou, Chih-Jen; Pan, Ru-Yu; Lin, Leou-Chyr; Shaw, Steven W.; Peng, Shao-Yu
Abstract: Assisted reproductive technology (ART) has been widely developed over the decades. This advanced technology has shown efficacy in the conception and breeding of an animal. However, several issues such as polyspermy, low maturation rate, and low development rate in vitro remain unresolved. Fallopian tube derived cells are proposed to promote the maturation and development of oocyte. This study aims to characterize porcine (PFTSC) and bovine fallopian tube stem cell (BFTSC) while comparing allogeneic and xenogeneic paracrine effects on porcine oocyte. FTSC of Taiwan yellow cattle ( B. indicus ) and porcine (Landrace x Yorkshire dam x Duroc) were isolated and identified. Conditioned media (Medium 199 or PZM-3) from porcine and bovine was collected and added to porcine cells during in vitro maturation (IVM) and in vitro culture (IVC). Both PFTSC and BFTSC expressed little CD44, CD105, and CD4. Both cells were induced to transform into chondrocytes, very few cells gave rise to osteocytes and adipocytes. IVM test showed a significant elevation of maturation rate in both groups (Porcine: 66.5 ± 3.5% > 55.9 ± 1.7%, p < .05; Bovine: 68.9 ± 2.3% > 55.9 ± 1.7%, p < .05). IVC test demonstrated markedly reduction of blastocyst in both groups. In a diluted conditioned medium with different concentration, 25% and 50% PFTSC showed a decrease in blastocyst rate which is significantly different, but BFTSC demonstrated no significant difference. PFTSC and BFTSC possessed properties of stem cells. Conditioned media from both PFTSC and BFTSC could improve maturation rate but not blastocyst rate in vitro. Highlights: Fallopian tube stem cell showed proliferative and differentiative potential. Both allogeneic and xenogeneic paracrine effects promoted maturation of oocyte. Xenogeneic cells limited development of embryo in late stage. Conditioned medium affected oocyte maturation and embryo development.